1993
DOI: 10.1111/j.1151-2916.1993.tb03950.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Observation of Crack Propagation in Piezoelectric Multilayer Actuators

Abstract: Crack propagation in multilayer piezoelectric actuators made of Pb((Ni,,3Nb,,,),Ti,Zr)0, ceramics with an interdigital electrode configuration was observed dynamically under an applied cyclic electric field using charge coupled device microscopy. The crack was observed only under a high electric field, and it healed under zero field. The crack was initiated at the internal electrode edge and propagated from the electrode edge in three directions. The electric-fieldinduced displacement was measured simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
92
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(92 citation statements)
references
References 3 publications
0
92
0
Order By: Relevance
“…The above mentioned events can be interpreted as a crack initiation process in multilayer ferroelectric actuators. Interestingly, this mechanism explains the experimental observations, in which the crack is initiated at the internal electrode edge, and it branches basically into three directions from the electrode edge which results in the delamination and oblique cracking of multilayer ferroelectric actuators [8,31,117].…”
Section: Crack Initiation Patterns At Electrode Edges In Multilayer Fmentioning
confidence: 69%
See 2 more Smart Citations
“…The above mentioned events can be interpreted as a crack initiation process in multilayer ferroelectric actuators. Interestingly, this mechanism explains the experimental observations, in which the crack is initiated at the internal electrode edge, and it branches basically into three directions from the electrode edge which results in the delamination and oblique cracking of multilayer ferroelectric actuators [8,31,117].…”
Section: Crack Initiation Patterns At Electrode Edges In Multilayer Fmentioning
confidence: 69%
“…Internal electrodes are commonly employed in the structures of multilayer actuators. Experiments reported that electrode edges are the main source of fracture in these actuators [8,31,56,71,72,117,146]. This is due to the generation of non-uniform electric fields in the vicinity of electrode edges, which in turn induce incompatible strain fields and hence concentrated stresses.…”
Section: Crack Initiation Patterns At Electrode Edges In Multilayer Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, the S-P 2 curves for the composition with We note that the Q value of lead-based electrostrictive material, such as Pb͑Mg, Nb͒O 3 -PbTiO 3 , is reported to be about 0.017. 23 That means the Q values of our materials are notably larger than that of lead-based electrostrictors. 7,8 The dielectric constant r and loss tan ␦ of the composition x = 0.30 were measured at different frequencies as a function of temperature as shown in Fig.…”
mentioning
confidence: 91%
“…Strain incompatibilities at the electrode boundary can result in stresses large enough to initiate cracks from nearby flaws 1-3 . Similarly, multilayer actuators, which are composed of several layers of partial internal electrodes, can develop stresses during switching operations that are high enough to generate cracks at electrode boundaries, thus limiting the effective lifetime of the device 4 . The reliability of partially electroded ferroelectrics can be improved by using thinner layers, which effectively reduces the volume of material exposed to high tensile stresses around the electrode edge during poling 2,3 .…”
Section: Introductionmentioning
confidence: 99%